CHARACTER EDUCATION MUHAMMADIYAH PATTERN (Case Study SMA Muhammadiyah 1 and MA Muallimin Yogyakarta) - Kuswono, Kuswono (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2013)
Abstrak: This  research   aims  to  find  out  the  sources   of character   education   at Islamic  schools,   character- building  values application  and actualization.   This research  was conducted  in SMA Mubammadiyah I Yogyakarta  and MA Muallimin  Muhammadiyah   Yogyakarta. The  result  of research   showed  that  teacher's   perception   on character   education  relied  on Islamic precepts   to create  akhakul  karimah-human    beings.  The  sources  of character   education   included Quran  and as=Sunnah/Hadist   as well  as Ijtihad.  The character   value  implantation   was  carried  out through   learning   in the  classroom,   precedents   from  figures,   teachers   and  peers,  well-behaving familiarization   in the presence  of rule and order, personality  report,  and extracurricular   activities  in knowledge,  skill, sport, art, and organization  fields. The form of character-building  values actualization emphasized   more  on the Islamic  activities  such as collectively   shalat,  reading  and reciting  Quran, social service, participating   actively  in IPM, hizbul wathan,  and tapak suci organizational   activities. In addition,   there  were  kader  inti/an,  mubalig  jumat,   mubalig   hijarah,   fasting,  Friday  sermon, becoming  the orator  in pengajian,   and flag ceremony.  Such these  activities  reflected  on religious, cooperative,   leadership,   loving-to-homeland,    social care, environmental   care, and creative  values.Keywords:  Education,  Character,  Muhammadiyah.